Determination of Zinc Sorption Properties of Gyttja, Leonardite and Compost - Kadir Saltalı; Muhammed Alhashemi (Turkish Journal of Agriculture: Food Science and Technology)
Leonardite and compost are used as soil conditioner materials. Gyttja is a material which contains 30-40% lime and 40-50% organic matter with a reserve of approximately 4.8 billion tons in Afşin-Elbistan Thermal Power Plant basin. These materials are used in the production of organomineral (OMG) fertilizers. Zinc (Zn) is one of the micronutrients that plants need. Available Zn deficiency is observed in approximately 49% of Turkish soils. The aim of this study was to determine the Zn adsorption properties of gyttja, leonardite and compost used in OMG fertilizer production. The study was conducted under laboratory conditions. In order to determine the optimum adsorption conditions, the effect of pH, particle size, temperature, shaking time and solution concentration were determined. Then, adsorption properties were determined using linear Langmuir isotherm under optimum conditions. According to Langmuir isotherm, the maximum sorption capacity (qmax) was found to be 14.10 mgg-1 for gyttja, 13.74 mgg-1 for leonardite and 15.67 mgg-1 for compost. In conclusion, Zn sorption values of gyttja, leonardite and compost were consistent with Langmuir and Freunlich isotherms. The maximum sorption capacity (qmax) of these materials is very close to each other. When these data are taken into consideration, it is seen that 1 kg of organic material can sorbed about 15 g Zn. It is useful to take these basic data into account in OMG fertilizer production and sustainable Zn fertilization.